2021
DOI: 10.3390/ijms222212506
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Advances in Gut Microbiome Modulation in Patients with Inflammatory Bowel Disease from Pediatrics to Adulthood

Abstract: There is mounting evidence that the gut microbiota plays an important role in the pathogenesis of inflammatory bowel disease (IBD). For the past decade, high throughput sequencing-based gut microbiome research has identified characteristic shifts in the composition of the intestinal microbiota in patients with IBD, suggesting that IBD results from alterations in the interactions between intestinal microbes and the host’s mucosal immune system. These studies have been the impetus for the development of new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 130 publications
(131 reference statements)
1
16
0
Order By: Relevance
“…Zhang et al showed that Lactobacillus plantarum significantly inhibits the production of intrinsic proinflammatory cytokines during the development of colitis in mice and improves intestinal stability, suggesting that this strain may be effective in controlling colitis symptoms and has therapeutic potential for IBD [80] . Yeo et al found that Lactobacillus rhamnosus strain LDTM 7511 attenuated inflammation and normalized bacterial dysbiosis in the inflamed gut of mice, suggesting that the probiotic has potential as an adjunctive treatment for IBD [81] . Bejarnason et al investigated the effects of probiotics on adult patients with UC and CD in remission or with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al showed that Lactobacillus plantarum significantly inhibits the production of intrinsic proinflammatory cytokines during the development of colitis in mice and improves intestinal stability, suggesting that this strain may be effective in controlling colitis symptoms and has therapeutic potential for IBD [80] . Yeo et al found that Lactobacillus rhamnosus strain LDTM 7511 attenuated inflammation and normalized bacterial dysbiosis in the inflamed gut of mice, suggesting that the probiotic has potential as an adjunctive treatment for IBD [81] . Bejarnason et al investigated the effects of probiotics on adult patients with UC and CD in remission or with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, IBD therapies attempt to target cytokines of the inflammatory cascade or systemic immunomodulation. However, these treatments are not always effective and may cause adverse side effects (Eindor-Abarbanel et al, 2021). As such, there are several clinical trials exploring the use of probiotics for the treatment of IBD (e.g.…”
Section: Other Targetsmentioning
confidence: 99%
“…Family members or friends and healthy volunteers are all suitable donors [ 144 ]. FMT was for the first time adopted in a patient with refractory UC who had improved conditions under endoscope with no symptoms during the 6-month follow-up after 3 months of treatment [ 145 ]. However, the clinical samples receiving FMT are still relatively small, and the clinical effectiveness is mainly evaluated by the relief of symptoms, which may be affected by many factors including donor screening, preparation of fecal bacterial fluid, transplantation route and frequency, severity of patient's condition and so on [ 145 ].…”
Section: Microrna and Ibdmentioning
confidence: 99%